Voice over IP gateway for internet telephony (2011)
This paper presents the design and implementation of a Voice over IP Gateway, with special attention to a better voice communication and adding functionalities to the existing Internet communication. It makes use of the Speex codec Software in reducing latency and jitter faced with most VOIP systems. It offers an alternative means of Internet communication and it is accessible anytime, anywhere in the World. Modem is used as its Hardware platform and the Gateway is implemented by running several programs on the Modem under the Windows environment. It also summarizes the evolution of IP Telephony products, and how the new designed gateway adds to pre-existing functionalities in terms of Voice communication improvement and standardization. This paper is aimed at building a web-based Internet telephony system that uses Internet protocol to transmit voice data over the Intranet. It not only looks at VoIP technologies, but also designs and implements a VoIP gateway that allows users to make telephone call over a PSTN network and an IP network and also solves the issues posed by the existing systems such as Limit in available bandwidth, Packet loss, Jitter, Echo, Security and Reliability. As a result, users will not need to buy and install any applications before making a phone call.